From subduction to collision and subduction again, the drivers of crustal-scale deformation in the Hellenides-Aegean region - Ferriere, Jacky; Jolivet, Laurent; Chanier, Frank (Comptes Rendus. Géoscience, 2023)
In the 60s, the Hellenic belt was taken as the “Geosyncline model”. Here we take a modern look at this Hellenic/Aegean region which as a concentrate encompasses all the main geodynamic processes known in orogens. This region documents the fundamental characteristics of the geodynamic processes related to mountain building, namely continental rifting, oceanic spreading, oceanic then continental subduction, collision i.e., closure of oceanic basins. In particular, the Mesozoic obduction events in northern Hellenides, and the effects of a still ongoing major extension linked to the active subduction under the Aegean domain.